What o say and to see in front of a shop window? (Palíndromo, 2020)
The text presents a visual analysis of a shop window of United Colors of Benetton store to investigate its communicational role in view of the aesthetic dimension of fashion. From the material constitution of the shop window, words and images are analyzed as elements that are related to the object of clothing and that allude to the metaphor of language. The text approach discusses the understanding of visual representations in the field of fashion and moves to the debate of ideology through semiotic studies.
Keywords: shop window; language; image; fashion